2018
DOI: 10.3389/fpsyt.2018.00090
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structural Covariance Network Topology in Remitted Posttraumatic Stress Disorder

Abstract: Posttraumatic stress disorder (PTSD) is a prevalent, chronic disorder with high psychiatric morbidity; however, a substantial portion of affected individuals experience remission after onset. Alterations in brain network topology derived from cortical thickness correlations are associated with PTSD, but the effects of remitted symptoms on network topology remain essentially unexplored. In this cross-sectional study, US military veterans (N = 317) were partitioned into three diagnostic groups, current PTSD (CUR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…Subsequently, age, age 2 , sex, site and mean whole-brain CT or SA estimates were regressed from the CT and SA estimates with a linear model (He et al, 2007) as explained in supplementary section 2.2.5. We performed SCN analyses by representing brain regions as nodes and CT/SA correlation coefficients as edges (He & Evans, 2010; Rubinov & Sporns, 2010a; Sun, Haswell, et al, 2018). Positive and negative coefficients were used to generate separate networks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, age, age 2 , sex, site and mean whole-brain CT or SA estimates were regressed from the CT and SA estimates with a linear model (He et al, 2007) as explained in supplementary section 2.2.5. We performed SCN analyses by representing brain regions as nodes and CT/SA correlation coefficients as edges (He & Evans, 2010; Rubinov & Sporns, 2010a; Sun, Haswell, et al, 2018). Positive and negative coefficients were used to generate separate networks.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, meta-analyses of structural neuroimaging in PTSD have applied voxel-based morphometry (VBM) and volume estimates of cortical regions to reveal gray matter volume differences in anterior cingulate cortex, insula, medial and ventromedial prefrontal cortex, orbitofrontal cortex, left temporal pole, rostral middle frontal gyrus, and superior frontal gyrus (Kuhn & Gallinat, 2013; Meng et al, 2016). However, there has been sparse literature on SCN in PTSD, consisting of two studies in adults with PTSD (Mueller et al, 2015; Sun, Davis, et al, 2018), two studies examining SCN in children or youth with PTSD (Sun, Haswell, et al, 2018; Sun, Peverill, et al, 2018), one study focused on SCN derived from diffusion tensor imaging (DTI) measures (Long et al, 2013), and finally one longitudinal study focused on SCN features predicting symptom onset following acute exposure to trauma (Harnett NG, Available online 7 August 2020). Findings were not consistent across studies, areas highlighted included bilateral anterior cingulate, bilateral superior frontal gyrus, right insula and occipital cortex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain networks involving the amygdala, hippocampus, and prefrontal cortex are also potential candidates (46). Imaging studies have shown centrality measures unique to individuals who were exposed to trauma but did not develop PTSD, as opposed to individuals who have developed PTSD after trauma exposure (104)(105)(106). Ideal studies to determine possible neural correlates of resilience would need to compare groups of individuals exposed to trauma with differential trajectories of PTSD development (45).…”
Section: Potential Translational Biomarkers Of Resilience In Clinical Trialsmentioning
confidence: 99%
“…Focusing on MIES scores in 26 post-9/11 veterans seeking care at a US. Veterans Affairs (VA) medical centre, neuroimaging findings (spontaneous resting-state brain fluctuations and functional connectivity) revealed dissociable neural underpinnings and behaviourally distinct components of morally injurious events and PTSD symptomatology (Sun et al, 2018 ). Notably, extant MI measures assess either exposure to morally injurious events or related symptoms, with a couple exceptions.…”
Section: Introductionmentioning
confidence: 99%